Pengaruh Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Ac Merek Daikin Pada PT Penta Mitra Aircon Karawaci - Rissa Hanny; Yuli Krisnawati (Journal Of Management, Business And Education, 2022)
The development of the business world is currently running very rapidly, which creates increasingly fierce competition among entrepreneurs. Technological advances are so rapid in various aspects of human life. The purpose of this study is to examine how much influence product quality has on purchasing decisions for Daikin Brand AC at PT Penta Mitra Aircon Karawaci Tangerang. Quantitative research methods were used in this study, which is based on the philosophy of positivism to examine certain populations or samples. The population of this research is consumers of PT Penta Mitra Aircon as many as 156 customers with a slovin' calculation and a precision of 5 percent, obtained 112 respondents as the final sample. The analytical method uses multiple linear regression analysis. The results of the study prove empirically that the magnitude of the influence of product quality on purchasing decisions of Daikin brand air conditioners is proven to have significance and a positive direction both partially and simultaneously. These product quality and price factors make a strong contribution of 60.08 percent to the decision to purchase Daikin Brand AC at PT Penta Mitra Aircon Karawaci Tangerang. The price factor has the highest influence compared to the product quality factor